Analisis Self Esteem Dengan Perilaku Verbal Abuse Pada Guru - Nurul Azmi Saragih (INDONESIAN COUNSELING AND PSYCHOLOGY, 2021)
This study aims to determine the analysis of the relationship between self-esteem and verbal abuse in teachers. The data collection instrument used to measure self-esteem and verbal abuse was a Likert scale. Self-esteem is measured based on aspects of self-esteem, namely strength, courage and virtue, on verbal abuse it is measured based on forms of verbal abuse, namely saying harsh words, slandering, threatening, scaring, insulting, exaggerating the mistakes of others. . The study population and the sample of this study were 33 respondents. The data analysis used is Simple Linear Regression Analysis. The results showed that there was a negative relationship between self-esteem and verbal abuse at the coefficient R = -0.467 and p = 0.003 means (p <0.05). This means that there is a negative relationship between self-esteem and verbal abuse behavior in teachers, so that the lower the self-esteem, the higher the verbal abuse.